2007
DOI: 10.3168/jds.2007-0107
|View full text |Cite
|
Sign up to set email alerts
|

Cow, Farm, and Management Factors During the Dry Period that Determine the Rate of Clinical Mastitis After Calving

Abstract: The purpose of the research was to investigate cow characteristics, farm facilities, and herd management strategies during the dry period to examine their joint influence on the rate of clinical mastitis after calving. Data were collected over a 2-yr period from 52 commercial dairy farms throughout England and Wales. Cows were separated for analysis into those housed for the dry period (8,710 cow-dry periods) and those at pasture (9,964 cow-dry periods). Multilevel models were used within a Bayesian framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
155
0
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(189 citation statements)
references
References 32 publications
14
155
0
17
Order By: Relevance
“…Similar values had already been used by other authors (BREEN et al, 2009). It is well established that cows with a SCC higher than 200,000 cells mL -1 are more likely to have an IMI than cows with a lower SCC (GREEN et al, 2007). In our study, we found out that Somaticell ® had a high sensitivity (90.59%) and low specificity (39.01%) for the threshold of 205,000 cells mL -1 , which indicates that it is a useful tool for detecting an increase in SCC, but possibly presenting some falsepositives results.…”
Section: Discussionsupporting
confidence: 72%
“…Similar values had already been used by other authors (BREEN et al, 2009). It is well established that cows with a SCC higher than 200,000 cells mL -1 are more likely to have an IMI than cows with a lower SCC (GREEN et al, 2007). In our study, we found out that Somaticell ® had a high sensitivity (90.59%) and low specificity (39.01%) for the threshold of 205,000 cells mL -1 , which indicates that it is a useful tool for detecting an increase in SCC, but possibly presenting some falsepositives results.…”
Section: Discussionsupporting
confidence: 72%
“…Somatic cell count is widely known to be an important risk factor for CM (e.g., Beaudeau et al, 1998;Suriyasathaporn et al, 2000;Green et al, 2007). Results from our study indicate that SCC in the previous month (SCC1) and SCC in the previous lactation (SCC2) are significant cow-specific risk factors for an increased IRCM.…”
Section: Discussionsupporting
confidence: 61%
“…To determine the association between previous SCC and IRCM in the current month of lactation, SCC in the previous month in lactation (SCC1) was determined. Also, SCC of the previous lactation was included (Whist and Østerå s, 2006;Green et al, 2007). This variable was defined as the geometric mean SCC from all available test-day records from the previous lactation (SCC2).…”
Section: Data Preparationmentioning
confidence: 99%
“…When the criteria for drying was daily milk production, the minimum milk production to maintain lactating cows was 5 L for 59% of the properties, and between 15 and 20 L for 13% of the interviewees. The extension of the dry period has an important impact on the cash flow of the property and the performance of the animals because it interferes with the relationship between productive (lactating cows) and unproductive animals (growing animals and dry cows) (Santschi et al, 2011), affects the incidence of metabolic problems in the post-calving period (Bachman and Schairer, 2003), influences mastitis prevention (Green et al, 2007), and also affects colostrum production (Machado Neto et al, 1995).…”
Section: Resultsmentioning
confidence: 99%